PEMIKIRAN PENDIDIKAN IKHWAN AL-SHAFA - Himayatul Izzati (Jurnal Al-Muta`aliyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2016)
The science of education is essentially a series of long experience of human activities throughout history education systematically arranged so easily understood, tested, applied and then developed from generation to generation. So that the concepts and theories of education that exist now or in the future, be developed in the future by experts in essence an attempt to continue thinking, experience and building a culture that has been developed by previous generations. For that examines the thinking of scholars, philosophers and scholars who are experts in the field of education remains a relevant activity in an effort to find the right education and the formulation can be applied in the present and in the future. This paper seeks to identify more concretely about who and how the formulation of educational thought of Ikhwan al-Safa, especially with regard to the role, dedication, ideas and contribution in developing a system and a new order of thought of Islamic education for the empowerment of its time, shown through their existence as a form of actualization of social function.